Knowledge, Attitudes, and Management of General Practitioners of the Hospital Districts of Ouagadougou about Migraine (Burkina Faso) - A. A. Dabilgou; A. Dravé; J. M. A. Kyelem; A. Zoma; C. Napon; A. Millogo; K. Karfo; J. Kaboré (Pain Research and Management)
Background. Migraine is a common neurological disorder characterized by severe headache attacks that may be debilitating. The objective of this study is to determine the knowledge and attitudes of general practitioners in the hospital districts of the city of Ouagadougou on migraine. Methods. This cross-sectional study was carried out in hospital districts of Ouagadougou. The data were collected during three months from February 1 to April 30, 2020. Results. The study included 116 general practitioners. Thirteen percent of them were suffering from migraine. All participants had previous experience with migraine diagnosis before the survey. Eighty percent of general practitioners had a good level of knowledge of ICDH-3 criteria (knowing 6-7 criteria). The most widely recognized IHS criteria were pulsatility quality (93.1%), photophobia or sonophobia (80.2%), and mild-to-moderate intensity (80%). Ninety-five (81.9%) general practitioners rarely ordered brain imaging. The most common acute treatments were nonsteroidal inflammatory drug (39.47%), paracetamol (44.74%), and derivate of ergot (3.95%). The most common preventive treatments were amitriptyline (27.8%), derivate of ergot (18.9%), and NSAID (16.7%). The majority of general practitioners (56.9%) have referred headache patients to a colleague or specialist. Conclusions. Our study found that diagnostic criteria and acute treatment of migraine were well known by the majority of general practitioners, in contrast of preventive treatment.